Re-visiting an old topic with a new approach: the case of ethical clothing. Issue 3 (10th July 2017) - Magnuson, Bryce; Reimers, Vaughan; Chao, Fred
Abstract : Purpose: A recent study by Reimers et al. (2016) suggests that the attitude-behaviour gap, as it applies to ethical clothing, may be due to academics having defined it differently to the way that consumers do. The purpose of this paper is to serve as a direct follow-up to that study by employing their consumer-based definition in order to help identify the clothing attributes that influence the purchase of ethical clothing. Design/methodology/approach: A consumer household sample in combination with a quantitative survey approach was used to collect the data, while structural equation modelling was used to analyse it. Findings: In spite of the ethical clothing context, only two of the four ethical clothing dimensions were found to influence consumer attitudes. In contrast, all three conventional dimensions were found to be significant. Originality/value: Ethical clothing has typically been operationalised using just two of these four dimensions. Ironically, one of the two dimensions often overlooked by academics, slow fashion, had one of the strongest influences on consumer attitudes. In addition, the cost of buying ethical clothing has often been defined in unidimensional terms; typically price. This study adopted a broader conceptualisation, defining it in terms of price, time and effort, and found it to serve as a salient influence over consumers' attitudes to ethical clothing.